1998
DOI: 10.1093/nar/26.3.796
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the DNA sequence that interacts with the gut-enriched Kruppel-like factor

Abstract: The gut-enriched Krüppel-like factor (GKLF) is a recently identified eukaryotic transcription factor that contains three C2H2zinc fingers. The amino acid sequence of the zinc finger portion of GKLF is closely related to several Krüppel proteins, including the lung Krüppel-like factor (LKLF), the erythroid Krüppel-like factor (EKLF) and the basic transcription element binding protein 2 (BTEB2). The DNA sequence to which GKLF binds has not been definitively established. In the present study we determined the DNA… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
176
0
1

Year Published

1999
1999
2018
2018

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 162 publications
(180 citation statements)
references
References 35 publications
3
176
0
1
Order By: Relevance
“…Whether this difference is specified by the Sp2 DNA-binding domain or is a consequence of our use of full-length protein for binding site selection studies remains to be determined. It is worth pointing out that although the Sp2 consensus sequence differs from those previously derived for Sp/XKLF family members, similar to the consensus sequences of zinc finger proteins, such as NGFI-A, NGFI-C, Zif268, and Egr3, the consensus Sp2-binding site is flanked by thymidine residues (35,39,47).…”
Section: Discussionmentioning
confidence: 87%
“…Whether this difference is specified by the Sp2 DNA-binding domain or is a consequence of our use of full-length protein for binding site selection studies remains to be determined. It is worth pointing out that although the Sp2 consensus sequence differs from those previously derived for Sp/XKLF family members, similar to the consensus sequences of zinc finger proteins, such as NGFI-A, NGFI-C, Zif268, and Egr3, the consensus Sp2-binding site is flanked by thymidine residues (35,39,47).…”
Section: Discussionmentioning
confidence: 87%
“…A consensus DNA binding sequence was empirically determined for KLF4 [11]. This sequence is present in many gene promoters and includes the CACCC element and the basic transcription element (BTE).…”
Section: Klf4 and Klf5 Bind To Similar Dna Sequences But Exert Opposimentioning
confidence: 99%
“…A 1.3-kbp sequence from the CYP2B promoter was shown to drive lung-specific reporter gene expression in a transgenic mice, and it was shown that C/EBP␣ and C/EBP␦ regulate CYP2B pulmonary expression during differentiation (19). In addition, the promoter contains a BTE site that has been demonstrated in numerous studies (35,36,47) to regulate CYP1A1 transcription. The BTE site of CYP1A1 has been recognized to bind a number of transcription factors from the Sp/XKLF family of factors, which are involved in both constitutive and tissuespecific regulation (48).…”
Section: Investigation Of the Binding Specificity Of Lung Nuclear Extmentioning
confidence: 99%